Equine enterolithiasis - DIAKAKIS (Ν.ΔΙΑΚΑΚΗΣ) N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Enterolithiasis is characterized by the presence of enteroliths in the large colon of horses with the ascending colon being the most common site of obstruction. Enteroliths are composed of ammonium magnesium phosphate, which is supplied both by the digestive processes intestinal bacteria and by feeds. The enteroliths typically form around a central nidus. Although enterolithiasis is seen all over the world, the most cases are reported from North America, and more specifically, California, South West Indiana and Florida. As far as breed is concerned, it affects predominantly Arab horses and rarely Quarter and Thoroughbreds. As far as age is concerned, it is usually seen in middle-aged horses. Although the pathogenesis of enterolithiasis is not fully understood, nutrition and heritability are believed to be a part in it. A rich diet in ammonium, magnesium and phosphorus predisposes to enterolith formation, as those elements are the main components of enteroliths. Clinical signs vary considerably and are rarely characteristic of the disease. Usually, the presence of the enterolith is free of symptoms unless it leads to obstruction. In most cases of enterolithiasis a small amount of faeces, air and the administered mineral oil could pass from the obstruction site. On the contrary, in complete obstructions the passage is closed, defecation is absent and no laxative can pass the obstruction site. The enterolith is rarely found by rectal examination. A history of recurrent colic might be connected to the presence of enteroliths that cause partial or temporary obstruction. The most accurate method for diagnosing enterolithiasis is abdominal radiography. The treatment of choice is the surgical removal of enteroliths, which has a favorable prognosis provided that the laparotomy is going to take place early in course of the disease, before the onset of peritonitis. Intestinal rupture, which rapidly leads to peritonitis, is the gravest and commonest complication. Other complications are colitis, leakage through the laparotomy site and peritonitis. In order to prevent reformation of enteroliths, the daily consumption of alfalfa hay has to be reduced dramatically and poor quality hay has to be administered.